Pusat-Pusat Keilmuan (Center of Islam learning) Paling Awal, Pertumbuhan dan Perkembangan Halaqah di Nusantara - Rodi, Rodi; Iswantir, Iswantir (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
The results of the research show that the halaqah institution is the oldest educational institution and has survived from the earliest times of Islam to the present. Halaqah, despite its simple form, plays an important role in the flow of knowledge transformation, especially Islamic knowledge in the development of Muslim society. Kingdom of Samuera Pasai, Lessons given in various halaqahs and other Islamic educational institutions are divided into two levels: First, the basic level consists of lessons in reading, writing, Arabic, Koran recitation, and practical worship. Second, the higher level with material on the sciences of fiqh, tasauf, kalam, and so on. Dayah functions as a kind of Islamic higher education. Because it is in this institution that the highest level of Islamic knowledge is studied by the students of knowledge. Which means a place of study or school, is in every village and has multiple functions, including: First, as a place to study the Koran. Second, as an elementary school, the material taught is writing and reading Arabic letters, religious knowledge, Malay language, morals and Islamic history. Under Sultan Ageng Tirtayasa Banten became very strongly oriented towards Mecca.